Pewarna Makanan dari Serangga (Cochineal) Menurut Perspektif Halal dalam Konteks Farmasi - Sultan, Siti Fatimah; Fathurohman, Oman (Schemata: Jurnal Pascasarjana UIN Mataram, 2024)
This article discusses the use of Cochineal, a food coloring derived from insects, in the context of a halal perspective in the pharmaceutical industry. The purpose of this article highlights the importance of halal compliance in the production of pharmaceutical products, including the use of halal additives such as Cochineal. This method presents a literature review of fatwas and research related to the halal status of Cochineal as a food ingredient. This review uses primary and secondary data, including direct surveys to Cochineal manufacturers and halal certification bodies, as well as scientific literature and reliable sources related to the halal status of Cochineal. The data was analyzed qualitatively, taking into account halal principles in Islam, pharmaceutical standards, and global food safety requirements. The study also utilized advanced analytical technologies, such as high-performance liquid chromatography (HPLC) and infrared spectroscopy, to detect and analyze the presence of non-halal contaminants in Cochineal food coloring. It was concluded that although Cochineal has been widely used as a food coloring, its halal status is still a matter of debate among scholars. Therefore, further research is needed to determine the halal status of Cochineal food coloring in halal perspective. Keywords: Cochineal, food coloring, halal, pharmaceutical, fatwa Artikel ini membahas penggunaan Cochineal, pewarna makanan yang berasal dari serangga, dalam konteks perspektif halal dalam industri farmasi. Tujuan artikel ini menyoroti pentingnya kepatuhan halal dalam produksi produk farmasi, termasuk penggunaan bahan tambahan halal seperti Cochineal. Metode ini menyajikan tinjauan literatur tentang fatwa dan penelitian yang berkaitan dengan status halal Cochineal sebagai bahan makanan. Kajian ini menggunakan data primer dan sekunder, termasuk survei langsung ke produsen Cochineal dan lembaga sertifikasi halal, serta literatur ilmiah dan sumber-sumber terpercaya terkait status halal Cochineal. Data dianalisis secara kualitatif, dengan mempertimbangkan prinsip-prinsip halal dalam Islam, standar farmasi, dan persyaratan keamanan pangan global. Penelitian ini juga memanfaatkan teknologi analisis canggih, seperti kromatografi cair kinerja tinggi (HPLC) dan spektroskopi inframerah, untuk mendeteksi dan menganalisis keberadaan kontaminan non-halal dalam pewarna makanan Cochineal. Kesimpulan bahwa meskipun Cochineal telah digunakan secara luas sebagai pewarna makanan, status kehalalannya masih menjadi perdebatan di antara para ulama. Oleh karena itu, penelitian lebih lanjut diperlukan untuk menentukan status kehalalan pewarna makanan Cochineal dalam perspektif halal. Kata kunci: Cochineal, pewarna makanan, halal, farmasi, fatwa